PERAN ASSESSMENT CENTER DALAM PENGEMBANGAN KARIER PERSONEL POLRI DI WILAYAH KEPOLISIAN DAERAH LAMPUNG - . Tatok (Universitas Bandar Lampung (UBL), 2017)
Factors that affect the development of the career personnel of the national police is the assessment center. Assessment center can be used to meet the needs of human resources reform in the governance environment in particular police agencies. Goals to be achieved, namely the existence of resources that has integrity, competent, professional, high-performing and prosperous, with carrying out the assessment center can build performance assessment system based on competencies, transparent and user friendly, the selection and procurement system that is transparent, fair and accountable, pattern development and training based on competency and Promotion Office. The aim in this study is to find out and analyse the role of the assessment center in the development of the career personnel of the national police in the region Police and the Lampung Region of factors that hampered and supporting the implementation of the assessment center in the development of the career personnel of the national police in the region police force areas of Lampung.The design used in this study is a qualitative research design, the techniques used in collecting data, among others, by way of observation, interview and documentation. Data analysis technique used is an interactive model of analysis that includes the reduction of the data, the presentation of data and verification.Based on the results of the study can then note that: (1) the role of the assessment center in the development of the career personnel of the national police in the region Police Region of Lampung, covering among other things some of the skills, knowledge and attitudes, of the overall results of the study could note that the assessment center is very effective in seeing the competencies possessed by the personnel of the national police be it skills, knowledge and attitude owned by the personnel of the national police , by looking at these indicators through the assessment center then the assesor can know the national police personnel in a comprehensive manner which is worthy or not given tenure (2) Factors restricting implementation of assessment center is a knowledge and information technical implementation assessment, budget constraints and facilities and infrastructure. Factors that have been in the implementation of the selection placement and Promotion Office of the national police personnel is the support of the leadership and cooperation with police in both the Center as well as existing in the area. Keywords: Assessment Center, Career Development